VolterraTeatro: trent’anni di un festival che attraversa il contemporaneo - Pratelli, Benedetta (Mimesis Journal, 2018)
In July 2016 the Tuscany festival VolterraTeatro celebrated its 30th edition, for the 16th time directed by Armando Punzo and its cultural association Carte Blanche. 16th and last: in 2017, in fact, the Director of the Compagnia della Fortezza renounced to participate to the new direction call for bids, denouncing an economic insecurity, that isn’t functional to an ongoing artistic project. The direction was commissioned to Andrea Kaemmerle and the Teatro Guascone. During thirty years Volterra Teatro was directed by four completely different personalities: Vittorio Gassman, Renato Nicolini, Roberto Bacci and Armando Punzo. Knowing a festival from its birth to its last developments it’s useful to understand not only its history but also the cultural background, the artistic trends and the politic ones as well of the historical period. In this article I’m going to give testimony of the VolterraTeatro’s evolution, following a specific thread: the local characterization of this phenomenon and its community dimension, that was, in my opinion, rather predominant.